Consumption of analgesics in American football, in the Federal State of Hesse, Germany: protocol of a cross-sectional study - Max Geraedts; Annika Viktoria Wienecke; Janis Evers (BMJ Open)
Introduction Considering the rising popularity of American football (AF) in Germany, particularly in the Federal State of Hesse, this study explores the concerning issue of analgesic consumption among players. The study aims to investigate analgesic use patterns and players’ awareness of risks, focusing on gender differences, medical care impact, positional intensity, league level and knowledge influence. The study aims to collect data that will contribute to the development of targeted preventive health measures, such as education and sensitising coaches during coaching licence courses and strategies to enhance medication safety in AF.Methods and analysis The cross-sectional study includes an online questionnaire targeting adult AF players in Hesse, Germany, during the 2024 season. Data collection, from October 2024 to April 2025, will cover dosage, timing, frequency of analgesic use and players’ knowledge of risks. The study will also explore the relationship between analgesic use and players’ skill levels, medical care availability, player activities and pain profiles. A pretest will ensure the questionnaire’s validity. Data analysis encompasses descriptive and logistic regression analyses to study the association between independent variables and analgesic use.Ethics and dissemination The responsible ethics committee of the faculty of Medicine at the Philipps University Marburg confirmed that no ethics vote was necessary if participants’ anonymity and research integrity are maintained. The results will be published in the form of an article and congress presentation. The findings aim to contribute to the development of tailored health measures, fostering a safer and healthier sporting environment for AF players in Germany.